Kejadian Gagal Ginjal Kronik pada Pasien Diabetes Melitus Tipe 2 - Mentari Putri Maharani; Kurniati , Intanri; Sidharti, Liana (Medula, 2024)
Diabetes is widely regarded as the most prevalent factor leading to end-stage renal disease. The rising prevalence of obesity and the growing number of elderly individuals will result in an increased population of individuals with diabetes who also have chronic kidney disease. This kidney disease can either be caused by diabetic nephropathy or have a different underlying cause. The management of diabetes and accurate assessment of kidney disease are influenced by the factors of ageing and obesity. Individuals suffering from both diabetes and chronic kidney disease account for a disproportionately large portion of medical care expenses. Individuals afflicted with diabetes and diabetic nephropathy exhibit heightened susceptibility to retinopathy and foot complications necessitating synchronized medical attention. Individuals with both diabetes and chronic kidney disease have a higher susceptibility to anaemia and metabolic bone disease compared to those without diabetes who are at the same stages of chronic kidney disease. Considering the high prevalence of kidney disease (30-40%) among individuals with diabetes, it is estimated that over 2% of the adult population falls into this category. Therefore, it is crucial to develop new surveillance models for providing care to individuals with both diabetes and kidney disease. Additionally, primary care teams, who are responsible for managing the majority of these individuals, should also be supported.